Dental Prosthetic Status and Prosthetic Needs of Patients Visiting Gandaki Medical College, Western Nepal - Tuladhar, Sapna Laxmi; Parajuli, U; Manandhar, P; Gurung, G (Journal of Gandaki Medical College-Nepal, 2018)
Introduction: The study of prosthetic status and prosthetic need will help us to find out the degree of treatment required in the population which will help to frame the health care services. Objective: The objective of the study was to find out the prosthetic status, prosthetic need in different age groups and their correlation with socio-economic status in patients visiting Department of Prosthodontics, College of Dental Surgery, Gandaki Medical College, Pokhara, Nepal. Materials and Methods: The patients visiting Department of Prosthodontics, College of Dental Surgery, Gandaki Medical College, Pokhara, Nepal were screened. The demographic profile of the patients was obtained and clinical examination for prosthetic status and prosthetic need was done based on WHO method. Results: There were total of 309 patients who visited the department during the study period. There were 133 (43%) male and 176 (57%) female patients. The majority of patients had no prosthesis in upper arch 78.6% and 83.8% in lower arch. The number of patients with replacement of missing teeth in upper arch was 66 (21.4%) and in lower arch were 50 (16.2%). There were 159 (51.5%) of patients requiring one or the other form of prosthesis in upper arch and 161 (52.1%) of patients in lower arch. Conclusion: The majority of patients had no prosthesis 78.6% in upper arch and 83.8% in lower arch. The need of prosthesis was 51.5% in upper arch and 52.1 % in lower arch.